Women's International League for Peace and Freedom At Courthouse Transit Stop Protesting Removal From Buses Their "Think Before You Register For The Draft" Signs - Watkins, Howard::::::::: (1982)
Protesters carrying Women's International League for Peace and Freedom banner and banned posters down City Hall walkway